Implementasi Pemungutan dan Penegakan Hukum Pajak Bumi Dan Bangunan Perdesaan dan Perkotaan di Kota Tasikmalaya (Berdasarkan Peraturan Daerah Kota Tasikmalaya Nomor 4 Tahun 2011 Tentang Pajak Daerah) - Rizki Aulia Muslim (UIN Sunan Kalijaga Yogyakarta, 2018)
The delegation of Land and Building Tax (PBB) from the central tax to regional taxes has an impact on the regions to carry out PBB collection and impose administrative sanctions on taxpayers who are not timely in paying the PBB. This research is an empirical and qualitative research type with an analysis based on the Regional Regulation of Tasikmalaya City Number 4 of 2011 concerning Regional Taxes. The results of the research obtained by the author are the Regional Government of Tasikmalaya City in handling the problem of collection and enforcement of land and building tax law delegated to the Regional Tax and Retribution Management Agency (BPPRD) of the City of Tasikmalaya using active and passive methods. Efforts made to impose sanctions on taxpayers are to provide administrative sanctions accompanied by actions to collect and apply alternative sanctions in the form of social sanctions.